ВІДМІННОСТІ ПРОФЕСІЙНО ВАЖЛИВИХ ЯКОСТЕЙ ТА ЇХ ВЗАЄМОЗВ’ЯЗКИ У ФАХІВЦІВ ЕКСТРЕНОЇ МЕДИЧНОЇ ДОПОМОГИ З РІЗНИМИ РІВНЯМИ ПРОФЕСІЙНОЇ КОМПЕТЕНТНОСТІ - Максим Удод (International Journal of Innovative Technologies in Social Science, 2020)
Comparison of emergency medical care and disaster medicine workers groups with different levels of professional aptitude and competency has given a possibility to find out the professionally significant features and acceptable levels of their manifestation. Among the professionally significant features on emotional and will level are indices of rigidity, excitability, activity, stress vulnerability, emotional stability, anxiety and depression inclination, tenseness and frustration vulnerability, emotional exhaustion, purposefulness, assertive and aggressive actions and avoidance in hard life situations. Among the professionally significant features on motivation and value level are indices of live value of rest, social braveness, psychological tact, inclination to mutual interpersonal knowledge and understanding, organizational skills and resilience in interpersonal relationship. Among the professionally significant features on reflection and activity level are indices of moral normativity, self-control, modeling, result checking and flexibility as individual self-regulation styles, depersonalization, professional achievements reduction, satisfaction from creativity in professional activity, satisfaction by work conditions, satisfaction by appreciation of personal contribution to collective professional activity. Satisfaction from professional activity is the important criterion of workers’ professional realization and it can be used as subjective criterion of workers’ professional aptitude. Workers with low level of professional aptitude and competency have difficulties with self-regulation, but they can gain resilience in interpersonal relationship by flexible and conscious adjustment. This aim can be realized by command work and compliance with the rules of professional subordination.